A Replicable Identity-Based Intervention Reduces the Black-White Suspension Gap at Scale. (April 2022) - Borman, Geoffrey D.; Pyne, Jaymes; Rozek, Christopher S.; Schmidt, Alex
Nationally, educators suspend Black students at greater rates than any other group. This disproportionality is fueled by stereotypes casting Black students as "troublemakers"—a label students too often internalize as part of their identities. Across two independent double-blind randomized field trials involving over 2, 000 seventh graders in 11 middle schools, we tested the efficacy of a brief intervention to buffer students from stereotypes and mitigate the racial suspension gap. The self-affirmation intervention helps students access positive aspects of their identities less associated with troublemaking in school. Confirmed in both trials, treatment effects cut Black-White suspension and office disciplinary referral gaps during seventh and eighth grade by approximately two thirds, with even greater impacts for Black students with prior infractions.